Mengatasi Masalah Parkir di Ibu Kota: Alternatif Solusi - Miming Miharja (Journal of Regional and City Planning, 1997)
As one of the promising tools within the traffic management schemes, parking control still need further research especiallu for its implementation in the developing countries city such as Jakarta. Specific characteristic of its physical, social, and economical nature need careful consideration before implementing parking control policy such as Rancangan Peraturan Daerah (Raperda) Perparkiran which apply the tariff variation system. This approach seems to hard to be implemented for this approach suffer from 'the lack of good acceptance' by the whole economic range of Jakarta people. So that, this article discusses some possible alternatives for parking control in Jakarta from the point of view. By discussing the advantages and disadvantages of each of the alternatives, hopely readers can be introduced to some of the possible alternative solutions.